Splayed Leg in Birds: Diagnosis, Therapy, and Prevention - Rief Ghulam Satriya Permana; Soedarmanto Indarjulianto; Yanuartono Yanuartono; Anggitya Nareswari; Shafa Adea Puspitadesy (Jurnal Sain Veteriner, 2023)
Splayed leg is a condition where the legs are stretched outwards or sideways from their normal position under the body which is often suffered by young birds. This disorder is usually left untreated, because it is considered as a permanent disability condition that cannot be treated without examining the cause. Some of the splayed legs in chicks can be improved by treating both their legs in the correct position. Early diagnosis of splayed leg and continued appropriate therapy is needed so that the condition of the foot can be restored to normal. Incorrect diagnosis and therapy will cause the bird's feet to become permanently disabled, so the bird will suffer for the rest of its life. The diagnosis and treatment of splayed leg cases have been developed with varying results. The purpose of this review is to evaluate the diagnosis, therapy, and prevention of the occurrence of splayed legs in birds, which can be used as a reference to improve bird welfare.